Proteomic and metabolomic analysis of GH deficiency-induced NAFLD in hypopituitarism: insights into oxidative stress - Zhang, Yuwen; Chen, Peizhan; Fang, Xuqian (Frontiers in Endocrinology, 2024)
Objective Individuals with hypopituitarism (HPs) have an increased risk of developing non-alcoholic fatty liver disease (NAFLD)/non-alcoholic steatohepatitis (NASH) due to growth hormone deficiency (GHD). We aimed to investigate the possible mechanisms underlying the relationship between GHD and NAFLD using proteomic and metabolomic insights. Methods Serum metabolic alternations were assessed in male HPs using untargeted metabolomics. A rat model of HP was established through hypophysectomy, followed by recombinant human growth hormone (rhGH) intervention. The mechanisms underlying GHD-mediated NAFLD were elucidated through the application of label-free proteomics and phosphorylation proteomics. Results Metabolomic analysis revealed that biomarkers of mitochondrial dysfunction and oxidative stress, such as alanine, lactate, and creatine, were significantly elevated in HPs compared to age-matched controls. In rats, hypophysectomy led to marked hepatic steatosis, lipid peroxidation, and reduced glutathione (GSH), which were subsequently modulated by rhGH replacement. Proteomic analysis identified cytochrome P450s, mitochondrial translation elongation, and PPARA activating genes as the major distinguishing pathways in hypophysectomized rats. The processes of fatty acid transport, synthesis, oxidation, and NADP metabolism were tightly described. An enhanced regulation of peroxisome β-oxidation and ω-oxidation, together with a decreased NADPH regeneration, may exacerbate oxidative stress. Phosphoproteome data showed downregulation of JAK2-STAT5B and upregulation of mTOR signaling pathway. Conclusions This study identified proteo-metabolomic signatures associated with the development of NAFLD in pituitary GHD. Evidence was found of oxidative stress imbalance resulting from abnormal fatty acid oxidation and NADPH regeneration, highlighting the role of GH deficiency in the development of NAFLD.